Evaluation of Antioxidant Activity of Two Indian Medicinal Plants - Hemalatha*, M. Padmaja, M. Sravanthi , K.P.J. (Journal of Phytology, 2011)
Adhatoda vasica Nees and Sesbania grandiflora (L.) Pers are the two important medicinal plants native to India. The aqueous leaf extracts of these two plants have been analysed for their free radical-scavenging activity in different in vitro systems, e.g. DPPH radical-scavenging activity, hydroxyl radical-scavenging activity in Fe3+/ascorbate/EDTA/H2O2 system, inhibition of lipid peroxidation induced by FeSO4 in egg yolk, metal chelating activity. The free radical scavenging activities were compared with standard antioxidants like butylated hydroxy toluene (BHT), ascorbic acid and EDTA. Total antioxidant activity was measured, based on the reduction of Mo (VI) to Mo(V) by the extract and subsequent formation of green phosphate/Mo(V) complex at acid pH and reducing power by Fe3+ - Fe2+ transformation in the presence of extracts. The content of total phenolics (expressed as mg of gallic acid equivalents/gm) and total flavonoids (expressed as mg of quercetin equivalent/gm) and ascorbic acid were determined along with antioxidant enzymes. The results indicated that A. vasica and S. grandiflora showed significant antioxidant activity in vitro. The enzymatic and non enzymatic antioxidants in A. vasica were found to be more than that of S. grandiflora, similarly the antioxidant and radical scavenging activities of A. vasica were found to be more significant than S. grandiflora.